2017
DOI: 10.1097/md.0000000000008007
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of gabapentin in reducing pain intensity and postoperative nausea and vomiting following laparoscopic cholecystectomy

Abstract: Background:It is unknown whether gabapentin is effective in reducing acute pain following laparoscopic cholecystectomy. The purpose of the current meta-analysis was to evaluate the efficacy of gabapentin in reducing pain intensity and postoperative nausea and vomiting (PONV) after laparoscopic cholecystectomy.Methods:All randomized controlled trials (RCTs) evaluating the efficacy of gabapentin in reducing pain intensity and PONV after laparoscopic cholecystectomy were searched on the following databases: PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Recently, several clinical trials have suggested the efficacy of GABA use for off-label pain conditions (e.g. chronic sciatica; irritable bowel syndrome) and for reducing acute and chronic postoperative pain and OPI use [50][51][52][53][54][55]. However, given the safety concerns about GABAs, there have been calls for placing more stringent regulations on gabapentin at the federal level and to include gabapentin monitoring in state prescription drug monitoring programs (PDMPs) to promote safety.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several clinical trials have suggested the efficacy of GABA use for off-label pain conditions (e.g. chronic sciatica; irritable bowel syndrome) and for reducing acute and chronic postoperative pain and OPI use [50][51][52][53][54][55]. However, given the safety concerns about GABAs, there have been calls for placing more stringent regulations on gabapentin at the federal level and to include gabapentin monitoring in state prescription drug monitoring programs (PDMPs) to promote safety.…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 , 30 ] And preoperative use of gabapentin was associated with a pain relieving in total knee and hip arthroplasty, spinal surgery and laparoscopic cholecystectomy. [ 31 35 ] Results from current meta-analysis indicated that gabapentin can decrease acute and chronic pain after breast cancer surgery. Results showed that gabapentin can decrease the pain scores by 16.14 and 27.33 points on 110-points after surgery and 24 hours, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…had concluded that gabapentin reduced pain scores at 12 and 24 h post-operatively in laparoscopic cholecystectomies. [ 1 ] In the studies included, the dosage varied from 300 to 1200 mg of gabapentin predominantly given as a single pre-medication dose only. The adverse events of gabapentin are dose-dependent as per the metaanalysis, and hence we used 600 mg of gabapentin.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of opioid and non-opioid analgesic drugs improves analgesic efficacy and reduces the side effects of individual drugs. [ 1 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation